Effect of Organic Fertilizer , Spraying with Nitrogen and Iron in Growth and Yield Swiss Chard - Al-Allaf, Mohammed Salim Ahmed; Hesham Saadaldeen Younis; Omar Younis Hasan (American Journal of Botany and Bioengineering, 2026)
The research was carried out on the vegetable field of the Agricultural Technical College in Mosul during the fall semester of 2025. Its objective was to examine the impact of applying two levels of organic fertilizer to the soil (400) Kg ha-1 , and effect of spraying with iron (0.10 g.L-1) and nitrogen (0.8 g.L-1). The organic fertilizer was mixed in during land preparation at rate of (4000) Kg ha-1. Iron and nitrogen spraying process was carried out with two sprays on the leaves, the first 35 days after planting and the second 10 days after the first spray. The studied treatments were organized in a completely randomized block design using a split-plot system with three replications. The post-harvest results for all traits were examined statistically in accordance with statistical design using (ANOVA) system. Comparisons were made between the mean treatments using Duncan's multiple range test at the likelihood of 5%. The treatment of organic fertilizer + foliar application of (10) g.L-1 iron + foliar application of (8) g.L-1 nitrogen was superior in the vegetative growth traits represented by leaf area, crown diameter, plant height, and number of leaves, and plant weight were (20.8 leaves, 75.1 cm, 42.3 mm, 5051 cm2, 2110 g) respectively.